Development of in situ bioprinting: A mini review - MacAdam, Aidan; Chaudry, Emaan; McTiernan, Christopher D.; Cortes, David; Suuronen, Erik J.; Alarcon, Emilio I. (Frontiers in Bioengineering and Biotechnology, 2022)
Bioprinting has rapidly progressed over the past decade. One branch of bioprinting known as in situ bioprinting has benefitted considerably from innovations in biofabrication. Unlike ex situ bioprinting, in situ bioprinting allows for biomaterials to be printed directly into or onto the target tissue/organ, eliminating the need to transfer pre-made three-dimensional constructs. In this mini-review, recent progress on in situ bioprinting, including bioink composition, in situ crosslinking strategies, and bioprinter functionality are examined. Future directions of in situ bioprinting are also discussed including the use of minimally invasive bioprinters to print tissues within the body.